Catalytic CO oxidation on B-doped and BN co-doped penta-graphene: a computational study. Issue 41 (11th October 2018) - Krishnan, Ranganathan; Wu, Shiuan-Yau; Chen, Hsin-Tsung
Abstract : The catalytic reaction of carbon monoxide oxidation on boron-doped and boron–nitrogen co-doped penta-graphene materials has been systematically studied by utilizing spin-polarized density functional theory (DFT) calculations. Abstract : The catalytic reaction of carbon monoxide oxidation on boron-doped and boron–nitrogen co-doped penta-graphene materials has been systematically studied by utilizing spin-polarized density functional theory (DFT) calculations. Various pathways including the Eley–Rideal (ER), Langmuir–Hinshelwood (LH), and tri-molecular Eley–Rideal (TER) mechanisms were considered in which the TER mechanism is a newly proposed reaction mechanism for CO oxidation. According to the calculation results, the ER, LH and TER mechanisms of CO oxidation can occur and compete with each other because of the related small overall reaction energy barriers (0.11–0.35 eV for the ER mechanism, 0.16–0.17 eV for the LH mechanism, and no activation energy for the TER mechanism). Our study helps to understand the various pathways for the CO oxidation process and suggests that both B-doped and BN co-doped penta-graphene sheets may serve as effective metal-free catalysts for low-temperature CO oxidation.